Nodule crushing: a novel technique to decentralize rhizobia inoculant technology and empower small-scale farmers to enhance legume production and income - Pudasaini, Roshan; Raizada, Manish N. (Frontiers in Sustainable Food Systems, 2024)
Millions of small scale legume farmers lack access to rhizobia bacterial inoculants that improve crop protein and yield, and minimize fossil-fuel based nitrogen fertilizers, through biological nitrogen fixation (BNF). BNF converts atmospheric nitrogen gas into ammonia, required to synthesize chlorophyll and amino acids. BNF is catalyzed by rhizobia that inhabit nodule organs in legume roots (e.g., soybean, cowpea, chickpeas, lentil, fava, peas, beans). Rhizobia inoculant access in remote communities is limited by centralized facilities to grow bacteria, inadequate transportation networks and refrigeration. Recently, we proposed that rhizobia inoculants can be diffused by farmers themselves, simply, by crushing nodules onto seeds, and demonstrated its efficacy under field conditions. A concern was whether nodules remain viable between growing seasons. Here we provide preliminary evidence that bean nodules, dried and stored at room temperature after 6 months, retain nodulation potential. We discuss: (1) the feasibility, constraints and risks of nodule crushing; (2) scaling up strategies; (3) entrepreneurship that benefits women farmers (e.g., nodule-selling microenterprises); and (4) empowering farmers to directly select, evolve and indigenize rhizobia for the first time. Finally, we prioritize research questions and encourage the formation of a global participatory research network, with the goal of decentralizing and democratizing rhizobia inoculants.